2011
DOI: 10.1016/j.taap.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione enzyme and selenoprotein polymorphisms associate with mercury biomarker levels in Michigan dental professionals

Abstract: Mercury is a potent toxicant of concern to both the general public and occupationally exposed workers (e.g., dentists). Recent studies suggest that several genes mediating the toxicokinetics of mercury are polymorphic in humans and may influence inter-individual variability in mercury accumulation. This work hypothesizes that polymorphisms in key glutathione synthesizing enzyme, glutathione s-transferase, and selenoprotein genes underlie inter-individual differences in mercury body burden as assessed by analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 32 publications
5
102
1
Order By: Relevance
“…GSTT1 encodes glutathione S-transferase theta-1, a member of a superfamily of enzymes that catalyze the conjugation of reduced glutathione (GSH) to a variety of electrophilic and hydrophilic ligands including Hg (Goodrich et al, 2011). GSTT1 has a deletion polymorphism that results in impaired (or null) catalytic activity that may be associated with increased Hg body burden (Gundacker et al, 2007, 2009; Schläwiche Engström et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GSTT1 encodes glutathione S-transferase theta-1, a member of a superfamily of enzymes that catalyze the conjugation of reduced glutathione (GSH) to a variety of electrophilic and hydrophilic ligands including Hg (Goodrich et al, 2011). GSTT1 has a deletion polymorphism that results in impaired (or null) catalytic activity that may be associated with increased Hg body burden (Gundacker et al, 2007, 2009; Schläwiche Engström et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Such studies are relevant, however, in light of recent findings (Basu, et al, 2013; Echeverria et al, 2005, 2006, 2010; Goodrich et al, 2011; Gundacker et al, 2007, 2009; Heyer et al, 2004, 2008, 2009; Schläwicke Engstrom et al, 2008; Wang et al, 2012) identifying common variants of numerous genes that modify the effects of Hg on neurologic functions and/or Hg handling in human subjects. Identification of genetic polymorphisms that affect Hg neurotoxicity is of particular importance with regard to assessment of Hg risks in children, who may be uniquely susceptible, compared with adults, because of their smaller body mass and more rapidly developing, hence more fragile, nervous and metabolic systems (Landrigan and Goldman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that metals-induced damage can be related to oxidative stress generation (17)(18)(19). Some studies have confirmed that occurrence of oxidative stress in metal exposure is relevant for human health assessment (20)(21)(22). Moreover, recent studies have confirmed a correlation between spirometry indexes and oxidative stress damage (23).…”
Section: Introductionmentioning
confidence: 92%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Numerous population studies have reported tachycardia, high blood pressure (BP), decreased heart rate variability (HRV), increase in the risk of stroke, and increased risk of total cardiovascular mortality. 17,[19][20][21][22][23][24][25] In a native population of Quebec (Canada), organic mercury exposure has been associated with increased resting HR but with no significant association with BP. 26 In a study conducted on 274 schoolchildren, an increased level of mercury in urine has been associated with elevated cholesterol level, which is a known risk factor for myocardial infarction, coronary disease, and CVD.…”
Section: Population Studiesmentioning
confidence: 99%